Structural method speech training with video media to PKK women in Medan Polonia district - harahap, Nurhayati; Widayati, Dwi; Basaria, Ida; Salliyanti, Salliyanti (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The Community Service Program is aimed at increasing the interest and speech ability of PKK women in Medan Polonia District and at the same time increasing reading interest, the ability to think logically and reasoning, the courage to express opinions, and to increase the creativity of PKK women in Medan Polonia District. The results of this training are: (1) Improving the ability of PKK mothers in giving public speeches. (2) Helps foster interest in reading PKK mothers for speech material. (3) Providing intensive speech training for PKK mothers. (4) Providing pocket books that can help PKK mothers understand good and correct speech methods and techniques. The results of this training have increased the insight of PKK mothers to give speeches properly and correctly in public and foster interest in reading because to search for speech topics requires insight into speech themes.